2017
DOI: 10.1016/j.celrep.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Impact of Alternative Splicing in Cancer

Abstract: Alternative splicing changes are frequently observed in cancer and are starting to be recognized as important signatures for tumor progression and therapy. However, their functional impact and relevance to tumorigenesis remain mostly unknown. We carried out a systematic analysis to characterize the potential functional consequences of alternative splicing changes in thousands of tumor samples. This analysis revealed that a subset of alternative splicing changes affect protein domain families that are frequentl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
374
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(387 citation statements)
references
References 62 publications
11
374
1
1
Order By: Relevance
“…Alternative splicing generates different mature mRNAs from a single gene through selection of different exons to increase transcriptome and proteome diversity . Aberrant alternative splicing events are commonly observed in cancer cells and contribute to tumor progression . Cancer‐specific mRNA transcripts, produced by interactions between cellular splicing factors and pre‐mRNAs, may result in either activation of oncogenes or inactivation of tumor‐suppressor genes, eventually leading to tumor invasion and metastasis .…”
mentioning
confidence: 99%
“…Alternative splicing generates different mature mRNAs from a single gene through selection of different exons to increase transcriptome and proteome diversity . Aberrant alternative splicing events are commonly observed in cancer cells and contribute to tumor progression . Cancer‐specific mRNA transcripts, produced by interactions between cellular splicing factors and pre‐mRNAs, may result in either activation of oncogenes or inactivation of tumor‐suppressor genes, eventually leading to tumor invasion and metastasis .…”
mentioning
confidence: 99%
“…For example, to the best of our knowledge, the TCGA study was one of the most comprehensive genomic characterizations of HNSCC, in which multiple, frequently mutated genes such as CDKN2A, TP53, FAT1, and AJUBA were identified predominantly in HPV-negative tumors. 9 The genome-wide mapping of alternative splicing variants also has been identified in a variety of tumors, including gastric, prostate, and breast cancer as well as other tumors. Therefore, in the current study, we used functional studies and demonstrated the role of a novel splice variant of LOXL2 in HPV-negative HNSCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Among patients with HNSCC, human papillomavirus (HPV)negative HNSCC has demonstrated a worse response to treatment and a poorer prognosis compared with HPV-positive HNSCC. 7,8 Given the importance of ASEs in regulating gene expression, the role of alternative splicing in tumorigenesis has attracted considerable interest, 9,10 and many cancer-related genes are considered to have functional diversity due to alternative splicing. In humans, it is estimated that >95% of multiexonic genes are alternatively spliced, which largely expands the complexity and diversity of human genes.…”
Section: Introductionmentioning
confidence: 99%
“…As with many other essential cellular processes, cancer cells have co‐opted alternative splicing to promote their survival and response to therapy. Many studies have revealed global dysregulation of splicing in cancer . For example, synonymous mutations occurring in consensus splice sites can alter intron recognition leading to intron retention and tumor suppressor inactivation .…”
Section: Introductionmentioning
confidence: 99%